Pd-loaded dual mesoporous silica nanoreactor and its preparation and application
By designing a dual mesoporous silica nanoreactor supported by Pd, the problem of easy leaching of metal nanoparticles during the catalysis process is solved, and efficient catalysis and excellent cycle stability are achieved.
Patent Information
- Application Number
- CN202211605154.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-14
AI Technical Summary
In existing mesoporous silica nanoreactors, metal nanoparticles are easily leaching from the shell mesopores during the catalysis process, affecting catalytic activity and material cyclic stability.
A double mesoporous silica nanoreactor loaded with Pd is used, which consists of two parts: the core and the shell. Both the core and the shell have a mesoporous structure. The Pd nanoparticles are loaded in the mesoporous on the core. The surface protection etching method ensures that the metal nanoparticles are stably sandwiched between the silica nanocore and the shell.
The stability and recycling performance of the catalyst are improved, the catalytic reaction efficiency reaches 99%, and can be successfully recovered six times without deactivation, with excellent catalytic activity and circulation stability.
Smart Images

Figure CN116020556B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to a Pd-loaded dual mesoporous silica nanoreactor and a preparation method and application thereof. Background Art
[0002] With the development of science and the advancement of technology, the petrochemical and catalytic industries have developed rapidly, which has led to an increasing demand for energy and various materials. Various chemical and chemical products have made immeasurable contributions to ensuring our quality of life. However, the massive consumption of energy has not only made the world face an increasingly severe energy crisis, but also brought about many environmental problems. Considering the future sustainable development, technology, low carbonization and greening have become the main development trends of the chemical industry in the future. Therefore, how to efficiently use non-renewable energy is of vital importance to human production and development.
[0003] The discovery and use of various types of high-efficiency catalytic materials have alleviated this situation to a great extent. Catalysts include carrier-loaded catalysts and unloaded catalysts. Compared with the same type of unloaded catalysts, catalysts that fix transition metal particles on nanoscale solid phase carriers show higher stability and environmental friendliness. The various nanocarriers used in supported nanocatalysts generally have the characteristics of low production cost, simple preparation process, scalability, and easy filtration so that they can be effectively recycled. Common materials that can be used as catalyst carriers include: carbon nanostructures (carbon nanotubes, carbon nitride, etc.), metal organic frameworks (MOFs), bionanomaterial carriers (pectin), metal oxide carriers (titanium dioxide, silicon dioxide), etc.
[0004] Among them, mesoporous silica materials have received extensive attention in the fields of medicine and catalysis due to their regular pore structure, narrow pore size distribution, high specific surface area and large pore volume. They are often used as drug carriers or catalytic carriers. When used as a catalytic carrier, the large specific surface area of mesoporous silica can improve the dispersion of transition metal particles loaded thereon, and the transition metal particles highly dispersed in its pores are not easy to aggregate, thereby improving the stability of nano-metal particles during reaction. Based on the advantages of mesoporous silica materials themselves, Chinese patent CN 102836710B discloses a method for preparing a silica core / mesoporous silica shell-supported gold nanoparticle microsphere based on a mesoporous silica carrier, which is a core-shell double-layer material, and the mesoporous structure on the silica shell layer helps the uniform distribution of gold nanoparticles, thereby improving the catalytic performance of the material. However, there is a more obvious problem with this material. Although it has a core-shell double-layer structure, the mesoporous structure only exists on the shell structure. Therefore, the metal nanoparticles are mainly loaded in the mesopores on the microsphere shell. Although it can initially prevent the nanoparticles from agglomerating, during the reaction process, such a loading method will cause the metal nanoparticles in the nanocatalyst to easily leach out from the shell mesopores during the catalytic process, which will ultimately affect not only the catalytic activity of the catalyst but also the cyclic stability of the material, resulting in a waste of catalytic materials, which is not in line with the current social trend of greening and sustainability.
[0005] Therefore, further searching for and developing new nanocomposite materials and preparing solid-supported catalysts with high stability and excellent recycling performance based on them are still important issues that need to be solved urgently. This will not only provide new and reliable ideas for the research and development of solid-phase supported catalysts, but will also be of great significance to the development and progress of the industry and even the country. Summary of the invention
[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a Pd-loaded dual mesoporous silica nanoreactor and its preparation and application. The overall preparation process of the catalytic material is simple, and the obtained material can complete the catalytic process of the Suzuki coupling reaction under a relatively simple environment, and the stability and recycling performance are guaranteed.
[0007] The present invention is achieved by: a method for preparing a Pd-loaded dual mesoporous silica nanoreactor, comprising the following steps:
[0008] (1) at 80°C, TEA was dispersed in deionized water, CTAB and sodium salicylate were added, and the mixture was stirred. Then, a silicon source and a silane coupling agent were added, and the mixture was stirred overnight. The mixture was washed with alcohol, dissolved in ETOH, and hydrochloric acid was added to remove excess CTAB to obtain mesoporous silica nanospheres.
[0009] (2) dispersing the product obtained in the previous step into a solvent, adding APTES dropwise, stirring, and obtaining aminated silica nanospheres dispersed in ETOH;
[0010] (3) adding the product obtained in the previous step into distilled water, and after ultrasonic dispersion, adding a THF solution of palladium acetate, vigorously stirring, adding a strong reducing agent, and centrifuging to collect the Pd-loaded mesoporous silica nanospheres;
[0011] (4) Surface modification of Pd-loaded mesoporous silica nanospheres using PVP under stirring conditions;
[0012] (5) dispersing the product obtained in the previous step in ethanol, adding a silicon source to re-wrap the silicon spheres in an alkaline environment, drying, dispersing in ultrapure water, and then modifying the nanoparticles with PVP, and the product is dispersed in deionized water;
[0013] (6) Injecting NaOH aqueous solution into the system to initiate etching, and controlling the etching time to obtain a shell with a target aperture.
[0014] Furthermore, the silicon sources used are TEOS and TMOS (tetramethoxysilane).
[0015] Furthermore, the particle size of the mesoporous silica nanospheres prepared in step (1) is 130-150 nm.
[0016] Furthermore, in step (2), the ratio of the amount of mesoporous silica nanospheres to that of APTES is 1:2-5.
[0017] Furthermore, the strong reducing agent used in step (3) is sodium borohydride, hydrazine hydrate or lithium borohydride.
[0018] Furthermore, in step (3), the molar ratio of the modified mesoporous silica nanospheres to Pd is 1:0.02-0.03.
[0019] Furthermore, in step (6), the temperature of the etching reaction is 20-30° C., and the etching time is 3 hours.
[0020] The Pd-loaded dual mesoporous silica nanoreactor prepared based on the above method is a spherical double-layer core-shell structure with a spherical particle size of 150-200nm. Both the core and the shell have mesoporous structures. Pd nanoparticles are loaded in the mesopores of the core. The pore size of the mesopores on the core is 3-8nm, and the diameter of the mesoporous channels on the shell is 12-15nm.
[0021] The above-mentioned Pd-loaded dual mesoporous silica nanoreactor can be used in catalytic Suzuki coupling reactions. The catalytic process is carried out in an air atmosphere. In an alcohol-water mixture, aromatic halides and aromatic boronic acids are used as reaction raw materials, potassium carbonate is used as a base, and the reaction is carried out at 70°C-100°C for 3-6 hours in the presence of the Pd-loaded dual mesoporous silica nanoreactor to separate the aromatic coupling product.
[0022] Furthermore, the catalytic reaction efficiency can reach 99% for the first time, and it is not deactivated after being recovered and recycled for six times, and the separation yield can still reach 92% at the sixth time.
[0023] Beneficial effects:
[0024] 1. The nanoreactor prepared in the present application consists of two parts, a "core" and a "shell". Both the core and the shell have a mesoporous structure. Pd nanoparticles are loaded in the mesopores of the core. The uniform mesoporous channels can not only evenly disperse the metal nanoparticles and increase the specific surface area of the material, but also prevent the metal nanoparticles from being inactivated due to agglomeration. The metal particles not loaded in the mesopores of the core can be stably sandwiched between the mesoporous silica nanocore and the mesoporous silica shell. This design can prevent the leaching of metal nanoparticles during the catalytic reaction to a large extent. The combination of the two greatly improves the catalytic performance of the material.
[0025] 2. The diameter of the mesoporous channels on the inner core of the nanoreactor with a dual mesoporous structure prepared in the present application is about 3-8 nm, and the diameter of the mesoporous channels on the outer shell is about 12-15 nm. The small channels on the inner core can firmly fix the metal particles in the inner core, and the large channels on the outer shell can allow the reactant molecules to enter and exit freely, showing the uniqueness and superiority of its structure;
[0026] 3. This application uses the method of "surface protection etching" to further encapsulate and etch the outer surface of the metal particles, thereby sandwiching the metal particles between the silica nanocore and the nanoporous silica shell. By controlling the etching time, the morphology of the mesopores on the shell can be actively controlled, which helps to obtain a catalytic material with a unique structure and superior performance;
[0027] 4. The reactor prepared in this application is used to catalyze the Suzuki coupling reaction, with a reaction efficiency of up to 99% and can be successfully recycled six times without deactivation, having excellent catalytic activity and cyclic stability;
[0028] 5. The preparation process of the nanoreactor disclosed in the present application is simple, the raw materials used are cheap and easily available, the cost is low, and it can be mass-produced, which has great industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1This is a microscopic morphology photograph of the "core" mesoporous silica prepared in Example 1;
[0030] Figure 2 This is a microscopic morphology photograph of the "core" prepared in Example 1 after loading Pd nanoparticles;
[0031] Figure 3 This is a microscopic morphology photograph of the core-shell double silica microspheres (unetched) prepared in Example 1;
[0032] Figure 4 It is a microscopic morphology photograph of the etching process in Example 1;
[0033] Figure 5 This is a microscopic picture of the Pd-loaded dual mesoporous silica nanoreactor prepared in Example 1;
[0034] Figure 6 The X-ray diffraction pattern of the Pd-loaded dual mesoporous silica nanoreactor prepared in Example 1;
[0035] Figure 7 FT-IR spectrum of the Pd-loaded dual mesoporous silica nanoreactor prepared in Example 1;
[0036] Figure 8 BET and XPS spectra of the Pd-loaded dual mesoporous silica nanoreactor prepared in Example 1;
[0037] Fig. 9 This is a cycle yield diagram of the Suzuki coupling reaction catalyzed by the nanoreactor prepared in Example 1;
[0038] Fig.10 The product of Suzuki coupling reaction obtained in the application example 1 H-NMR spectrum DETAILED DESCRIPTION
[0039] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0040] Example 1. Preparation of Pd-loaded dual mesoporous silica nanoreactor
[0041] (1) Disperse 0.068 g of TEA (triethanolamine) in 25 mL of deionized water at 80 °C, stir for 30 min, then add 0.38 g of CTAB (hexadecyltriethylammonium bromide) and 0.168 g of sodium salicylate to the system, stir at 300 rpm for 1 h, add 2 mL of TEOS (tetraethyl orthosilicate) and 0.6 mL of BTSE (1,2-bis(triethoxysilyl)ethane), stir overnight for 12 h, wash the sample twice with alcohol, dry it in an oven, add 200 mL of ETOH to the dried sample and transfer it to a clean glass bottle, add 400 μL of hydrochloric acid to remove CTAB at 60 °C, repeat the operation three times, each time for 3 h, 3 h, and 12 h, to obtain mesoporous silica nanospheres (MS) as the core;
[0042] (2) 300 mg of mesoporous silica nanospheres were transferred to 100 mL of isopropanol, and 1.5 mL of APTES (γ-aminopropyltriethoxysilane) was added dropwise for modification (the molar ratio of mesoporous silica nanospheres to APTES was 1:2), and stirred at 500 rpm at 80 °C for 12 h to obtain amino-modified mesoporous silica nanospheres (MS-NH2), which were then dispersed in 30 mL of ETOH;
[0043] (3) The product obtained in the previous step was added to 30 mL of distilled water, ultrasonically dispersed for 15 min, and 10 mL of THF (tetrahydrofuran) solution of palladium acetate (11.17 mg mL -1 ), vigorously stirred for 24 h, a sufficient amount of NaBH4 aqueous solution was added dropwise to the solution for sufficient reaction for 3 h, and then the Pd-loaded mesoporous silica nanoparticles were collected by centrifugation (8000 rpm);
[0044] (4) Under magnetic stirring conditions, the product obtained in the previous step was added to 30 mL of deionized water to form a silica colloidal solution, and then mixed with 1 g of polyvinyl pyrrolidone (PVP, Mw ~ 55000). After reflux at 100 ° C for 3 h, the solution was cooled to room temperature, and the PVP-modified nanoparticles were collected by centrifugation and placed in an oven for drying;
[0045] (5) The product obtained in the previous step was dispersed in 100 mL of ethanol, stirred magnetically, and then 12 mL of H2O, 5 mL of ammonium hydroxide solution and 2 mL of TEOS were added in sequence. After keeping at room temperature for 3 hours, the product was collected by centrifugation and dried. The dried product was dispersed in 30 mL of ultrapure water and mixed with 2 g of PVP (Mw ~ 55000). After reflux at 100 ° C for 3 hours, the solution was cooled to room temperature, washed twice by centrifugation, and dispersed in 30 mL of deionized water;
[0046] (6) NaOH aqueous solution (5 mL, 0.20 g / mL) was injected into the system to initiate etching. The etching process was carried out at 30° C. After etching for a period of time, the product particles were collected by centrifugation, washed three times with ultrapure water, and dried for later use.
[0047] Figure 1 This is a microscopic morphology photograph of the mesoporous silica "core" prepared in step (2). From the particle size analysis report, it can be seen that the diameter of the prepared microspheres (MS) is about 100nm-150nm, and the mesopore diameter is about 3-8nm.
[0048] Figure 2 This is a microscopic morphology photograph of the Pd-loaded mesoporous silica "core" obtained in step (3). It can be seen from the figure that the metal nanoparticles are dispersed relatively evenly on the carrier.
[0049] Figure 3 This is a microscopic morphology photograph of the unetched core-shell structured nanoparticles obtained in step (5). As the amount of TEOS added increases, the diameter of the catalyst increases.
[0050] Figure 4 To take a microscopic morphology photo of the particles during the etching process, we mixed the prepared MS-NH2@Pd-SiO2 with the PVP solution and then refluxed it at 100°C to allow the PVP molecules to be fully adsorbed on the surface. NaOH was added to initiate an etching reaction. As the etching time increased, the morphology of the catalyst continued to change. When the etching solution was just added to the high-speed stirring reaction system, the etching began, and the reaction system was monitored at the same time. As shown in the figure, after 1 hour (a sub-picture), the silica showed a microporous structure. After 2 hours (b sub-picture), the pore size gradually increased. When the etching time was about 3 hours (c sub-picture), it showed an obvious macroporous structure. When the etching time reached 6 hours (d sub-picture), the morphology and structure of the catalyst were completely destroyed. Therefore, in order to ultimately obtain a high-performance catalyst material, the shell material can allow the reactant molecules to freely enter and exit through the mesopores on it, and prevent the core from detaching. It is necessary to properly control the etching time to prevent the mesoporous structure on the shell from being destroyed and affecting the performance of the microspheres. After this test, this application selected 3h as the optimal etching time.
[0051] Figure 5 This is a microscopic photograph of the Pd-loaded dual mesoporous silica nanocatalyst (MS-NH2@Pd-MS) finally obtained in this example. It can be seen from the figure that the metal particles are successfully loaded on the carrier and are evenly distributed. The spherical particle size is 150-200nm, and the diameter of the mesoporous channels on the shell is about 12-15nm.
[0052] The XRD characterization of the final product is as follows Figure 6As shown, the results show that there is a wide characteristic peak at 2θ=23°, corresponding to the plane (211) of the silica sphere material. XRD shows three peaks, corresponding to the planes (111), (200), and (220) of Pd, and the diffraction intensity of Pd nanoparticles is relatively low, with obvious peak broadening. This is expected for small Pd nanoparticles, because the Pd nanoparticles are in a highly dispersed state in the resulting catalyst, which may also be the reason for the relatively low Pd diffraction intensity. With further coating and etching of the silica shell, the Pd diffraction peak intensity of MS-NH2@Pd-MS becomes lower, which is also within expectations. Therefore, it can be concluded from the XRD analysis that the Pd nanoparticles on the silica sphere carrier remain stable and are successfully loaded on the carrier.
[0053] The Fourier transform infrared spectrum (FI-IR) of the final product is as follows: Figure 7 As shown, at 3416cm -1 The absorption band at 1103 cm -1 The absorption peak at 3378-3370cm in the infrared spectrum of APTES-modified silica is higher than that of unmodified APTES-modified silica. -1 and 3308-3300cm -1 The stretching vibration of NH appears at 1595-1590cm -1 The bending vibration of NH appears between 2980-2977cm -1 The CH stretching vibration of CH3 appears between 2935-2930cm -1 These results indicate that the amino groups were successfully modified on the surface of the silica spheres and no significant changes occurred after in situ reduction of Pd.
[0054] The final product was subjected to BET test and XPS element characterization, and the results are as follows: Figure 8 As shown in the figure, it can be seen that there is an obvious IV type adsorption curve, which also shows that amorphous silica is a typical mesoporous material with a macroporous structure. 3d Peak (c) shows that the binding energies of 335.8 eV and 341.2 eV originate from the 3d 5 / 2 and 3D 3 / 2 Peaks at 337.7eV and 343.0eV are the 3d 5 / 2 and 3D 3 / 2 , which can be attributed to the oxidation of Pd to PdO. Since the Pd nanoparticles are encapsulated in an ordered macroporous silica shell, the intensity of the XPS peak is weak.
[0055] Example 2: Preparation of Pd-loaded dual mesoporous silica nanoreactor
[0056] (1) Disperse 0.0068 g TEA (triethanolamine) in 25 mL deionized water at 80 °C, stir for 30 min, then add 0.038 g CTAB and 0.0168 g sodium salicylate to the system, stir at 300 rpm for 1 h, add 0.2 mL TEOS (tetraethyl orthosilicate) and 0.06 mL BTSE, stir overnight for 12 h, wash the sample with alcohol twice, dry it in an oven, add 200 mL ETOH to the dried sample and transfer it to a clean glass bottle, add 400 μL hydrochloric acid to remove CTAB at 60 °C, repeat the operation three times, each time for 3 h, 3 h, and 12 h, to obtain mesoporous silica nanospheres (MS);
[0057] (2) 30 mg of mesoporous silica nanospheres were transferred to isopropanol (100 mL), and 0.15 mL of APTES was added dropwise for modification (the molar ratio of mesoporous silica nanospheres to APTES was 1:2), and stirred at 500 rpm at 80 °C for 12 h to obtain amino-modified mesoporous silica nanospheres (MS-NH2), which were then dispersed in 30 mL of ETOH;
[0058] (3) The product obtained in the previous step was added to 30 mL of distilled water, ultrasonically dispersed for 15 min, and 10 mL of THF solution of palladium acetate (1.117 mg ml -1 ), vigorously stirred for 24 h, a sufficient amount of NaBH4 aqueous solution was added dropwise to the solution for sufficient reaction for 3 h, and then the Pd-loaded mesoporous silica nanoparticles were collected by centrifugation (8000 rpm);
[0059] (4) Under magnetic stirring conditions, the product obtained in the previous step was added to 30 mL of deionized water to form a silica colloidal solution, and mixed with 0.1 g of PVP (Mw ~ 55000). After reflux at 100 ° C for 3 h, the solution was cooled to room temperature, and the PVP-treated nanoparticles were collected by centrifugation and placed in an oven for drying;
[0060] (5) Disperse the product obtained in the previous step in 100 mL of ethanol, stir magnetically, then add 12 mL of H2O, 5 mL of ammonium hydroxide solution and 0.2 mL of TEOS in sequence, keep at room temperature for 3 hours, collect the product by centrifugation and dry it. Disperse the dried product with 30 mL of ultrapure water and mix it with 0.2 g of PVP (Mw ~ 55000). After refluxing at 100 ° C for 3 hours, the solution is cooled to room temperature, washed twice by centrifugation, and dispersed in 30 mL of deionized water;
[0061] (6) NaOH aqueous solution (5 mL, 0.20 g / mL) was injected into the system to initiate etching. After etching for 3 h, the product particles were collected by centrifugation, washed three times with ultrapure water, and dried for later use.
[0062] The microstructure of the catalyst material prepared in this embodiment is similar to that in Embodiment 1, both of which are double mesoporous spherical structures of core and shell structures, that is, both the core and the shell have mesoporous structures, and Pd is loaded in the mesopores on the core. The particle size of the obtained catalyst material is between 130-150nm.
[0063] Example 3: Preparation of Pd-loaded dual mesoporous silica nanoreactor
[0064] (1) Disperse 0.136 g TEA (triethanolamine) in 25 mL deionized water at 80 °C, stir for 30 min, then add 0.76 g CTAB and 0.336 g sodium salicylate to the system, stir at 300 rpm for 1 h, add 4 mL TEOS (tetraethyl orthosilicate) and 1.2 mL BTSE, stir overnight for 12 h, wash the sample with alcohol twice, dry it in an oven, add 200 mL ETOH to the dried sample and transfer it to a clean glass bottle, add 400 μL hydrochloric acid to remove CTAB at 60 °C, repeat the operation three times, each time for 3 h, 3 h, and 12 h, to obtain mesoporous silica nanospheres (MS);
[0065] (2) 600 mg of mesoporous silica nanospheres were transferred to 100 mL of isopropanol, 3 mL of APTES was added dropwise for modification, and the mixture was stirred at 500 rpm at 80 °C for 12 h to obtain amino-modified mesoporous silica nanospheres (MS-NH2), which were then dispersed in 30 mL of ETOH;
[0066] (3) The product obtained in the previous step was added to 30 mL of distilled water, ultrasonically dispersed for 15 min, and 10 mL of THF solution of palladium acetate (22.34 mg mL -1 ), vigorously stirred for 24 h, a sufficient amount of NaBH4 aqueous solution was added dropwise to the solution for sufficient reaction for 3 h, and then the Pd-loaded mesoporous silica nanoparticles were collected by centrifugation (8000 rpm);
[0067] (4) Under magnetic stirring conditions, the product obtained in the previous step was added to 30 mL of deionized water to form a silica colloidal solution, and then mixed with 2 g of PVP (Mw ~ 55000). After reflux at 100 ° C for 3 h, the solution was cooled to room temperature, and the PVP-modified nanoparticles were collected by centrifugation and placed in an oven for drying;
[0068] (5) The product obtained in the previous step was dispersed in 100 mL of ethanol, stirred magnetically, and then 12 mL of H2O, 5 mL of ammonium hydroxide solution and 4 mL of TEOS were added in sequence, kept at room temperature for 3 hours, centrifuged to collect the product, and dried. The dried product was dispersed in 30 mL of ultrapure water and mixed with 4 g of PVP (Mw ~ 55000), refluxed at 100 ° C for 3 hours, and the solution was cooled to room temperature, centrifuged and washed twice, and dispersed in 30 mL of deionized water;
[0069] (6) NaOH aqueous solution (5 mL, 0.4 g / mL) was injected into the system to initiate etching. After etching for 3 h, the product particles were collected by centrifugation, washed three times with ultrapure water, and dried for later use.
[0070] The microscopic morphology of the catalyst material prepared in this example is similar to that of the product obtained in Example 1. The particle size of the synthesized catalyst material is between 130-150 nm. The material has a double mesoporous spherical structure, and Pd is loaded in the mesopores on the core. It can be seen that the catalyst is not only suitable for small-dose preparation, but can also be successfully synthesized after increasing the amount of reactants, and is suitable for large-scale production.
[0071] Application example: The Pd-loaded dual mesoporous silica nanoreactor prepared in Example 1 is used as a catalyst to catalyze the Suzuki coupling reaction to test the catalytic performance of the product. The specific operation is as follows:
[0072] 20 mg of MS-NH2@Pd-MS, 0.3 mmol of p-bromotoluene, 0.36 mmol of phenylboric acid and 0.75 mmol of potassium carbonate were added into a dry Schlenk tube, replaced with nitrogen three times, 3 mL of an alcohol-water mixture (the volume ratio of alcohol to water is 1:1) was added, heated to 70°C, stirred for 3 h, and cooled to room temperature; the supernatant was taken by centrifugation, and the precipitate was washed with 15 mL*3 times of dichloromethane, the organic phases were combined, washed with saturated brine, dried, rotary evaporated, separated by column chromatography, and purified to obtain biphenyl derivatives.
[0073]
[0074] The first separation yield of the reaction reached 99%. After the catalyst was recovered by centrifugation, the separation yield dropped to 92% after the reaction was repeated 6 times under the same reaction conditions. The yield results are shown in Fig. 9 , which proves that the catalytic material prepared in Example 1 has good catalytic performance and cyclic catalytic ability. Fig.10 The obtained Suzuki coupling reaction product 1 H-NMR spectrum shows that the reaction was successful and the biphenyl derivative was obtained as the product.
[0075] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a Pd-loaded dual mesoporous silica nanoreactor, characterized in that: The steps include: (1) at 80°C, TEA was dispersed in deionized water, CTAB and sodium salicylate were added, and the mixture was stirred. Then, a silicon source and a silane coupling agent were added, and the mixture was stirred overnight. The mixture was washed with alcohol, dissolved in ETOH, and hydrochloric acid was added to remove excess CTAB to obtain mesoporous silica nanospheres. (2) dispersing the product obtained in the previous step into a solvent, adding APTES dropwise, stirring, and obtaining aminated silica nanospheres dispersed in ETOH; (3) adding the product obtained in the previous step into distilled water, and after ultrasonic dispersion, adding a THF solution of palladium acetate, vigorously stirring, adding a strong reducing agent, and centrifuging to collect the Pd-loaded mesoporous silica nanospheres; (4) Surface modification of Pd-loaded mesoporous silica nanospheres using PVP under stirring conditions; (5) dispersing the product obtained in the previous step in ethanol, adding a silicon source to re-wrap the silicon spheres in an alkaline environment, drying, dispersing in ultrapure water, and then modifying the nanoparticles with PVP, and the product is dispersed in deionized water; (6) Injecting NaOH aqueous solution into the system to initiate etching, the etching reaction temperature is 20-30°C, the etching time is 3 h, and a shell with a target pore size is obtained; The nanoreactor prepared according to the above steps is a spherical double-layer core-shell structure, with mesoporous structures on both the core and the shell. Pd nanoparticles are loaded in the mesopores of the core, and the mesoporous channels on the shell allow reactant molecules to enter and exit freely.
2. The method for preparing the Pd-loaded dual mesoporous silica nanoreactor according to claim 1, characterized in that: The silicon source used is TEOS or TMOS.
3. The method for preparing the Pd-loaded dual mesoporous silica nanoreactor according to claim 1, characterized in that: The particle size of the mesoporous silica nanospheres prepared in step (1) is 130-150 nm.
4. The method for preparing the Pd-loaded dual mesoporous silica nanoreactor according to claim 1, characterized in that: In step (2), the molar ratio of the mesoporous silica nanospheres to the APTES is 1:2-5.
5. The method for preparing the Pd-loaded dual mesoporous silica nanoreactor according to claim 1, characterized in that: The strong reducing agent used in step (3) is sodium borohydride, hydrazine hydrate or lithium borohydride.
6. The method for preparing the Pd-loaded dual mesoporous silica nanoreactor according to claim 1, characterized in that: In step (3), the molar ratio of the modified mesoporous silica nanospheres to Pd is 1:0.02-0.
03.
7. A Pd-loaded dual mesoporous silica nanoreactor, characterized in that: It is prepared according to the preparation method of a Pd-loaded dual mesoporous silica nanoreactor according to any one of claims 1 to 6. The nanoreactor is a spherical double-layer core-shell structure with a spherical particle size of 150-200nm. Both the core and the shell have a mesoporous structure. Pd nanoparticles are loaded in the mesopores of the core. The pore size of the mesopores on the core is 3-8 nm, and the diameter of the mesoporous channels on the shell is 12-15 nm.
8. Use of the Pd-loaded dual mesoporous silica nanoreactor according to claim 7 in catalyzing Suzuki coupling reaction, characterized in that: The catalytic process is carried out under an air atmosphere, in an alcohol-water mixture, with aromatic halides and aromatic boronic acids as reaction raw materials, potassium carbonate as base, in the presence of a Pd-loaded dual mesoporous silica nanoreactor, at 70°C-100°C for 3-6 hours, and the aromatic coupling product can be separated.
9. Use of the Pd-loaded dual mesoporous silica nanoreactor according to claim 8 in catalyzing Suzuki coupling reaction, characterized in that: The catalytic reaction efficiency can reach 99% for the first time, and it remains intact after being recovered and recycled for six times, with the separation yield still reaching 92% for the sixth time.
Citation Information
Patent Citations
Preparation method of silica core / mesoporous silica shell-supported gold nano-particle microspheres
CN102836710B
Preparation method of silica core / mesoporous silica shell-supported gold nano-particle microspheres
CN102836710A